Sports literature - Brady, John Joseph, 1942-; Hall, Jim, 1942- (New York, McGraw-Hill, 1974)
An anthology exploring the athletic experience through poetry, essays, and stories written by sports columnists, literary figures, and athletes themselves.
Keywords: Sports stories; Sports; Sports -- Fiction